Avoiding trap states in poly(n-vinylcarbazole) thin films - Valadares, M.; Calado, H. D. R.; Araujo, K. A. S.; Guimarães, P. S. S.; Cury, L. A.; Akcelrud, L.; Sanvitto, D.; Giorgi, M. de (Organic Electronics, 2012)
Optical properties of poly(n-vinylcarbazole) (PVK) thin films are revisited. Steady-state emission spectra put in evidence a strong red band whose intensity increases with decreasing temperature when the solid state PVK film is excited by a continuous 375 nm laser line. This red band is assigned to the emission from PVK aggregate states which act as trap states for the monomeric PVK triplet high energy (blue) excitons. At the same low temperatures, these trap states can be avoided when the excitation of the PVK film is made by a 355 nm pulsed laser line with 10 Hz repetition rate. The red band was also observed to compete with the emission of guest poly(3-octadecylthiophene) (PODT) molecules in a PVK/PODT sequential bilayer structure. Different optical geometries enabled us to show that the exciton energy transfer effect from PVK donor to PODT acceptor states dominates the scenario in the bilayer structure, suppressing almost completely the trap state emissions.
Keywords: Triplet trap states; PVK; Aggregates; Exciton energy transfer; PVK/PODT adjacent bilayerpt-BR